KELANCARAN PROSEDURAL MATEMATIS MATERI OPERASI HITUNG BENTUK ALJABAR DITINJAU DARI PROKRASTINASI SISWA DI SMP - Dini Maulida Sari; Agung Hartoyo; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this research was to describe procedural fluency of algebraic operation in terms of student academic procrastination SMP Negeri 4 Ketapang. The form of this research was a case study which used a descriptive qualitative method. There were 25 students of grade VII A as the subject of this research. The object of this research was procedural fluency of algebraic operation in terms of high, middle, and low student academic procrastination condition. The technique of data collection in this research was procedural fluency test, student academic procrastination questionnaire, and unstructured interview. The data analysis was in the form of procedural fluency test, student academic procrastination questionnaire, and interview. The result of the descriptive analysis showed that student with a high condition of academic procrastination have low and middle condition of mathematic procedural fluency. Student with a middle condition of academic procrastination had middle and high condition of mathematic procedural fluency. Student with a low condition of academic procrastination had middle and high condition of mathematic procedural fluency.Keywords : Academic Procrastination, Algebraic Operation, Procedural Fluency